Epidemiological and clinical profile of hepatitis B infection in ART-naïve people living with HIV in Maputo, Mozambique: a cross-sectional study - Esperanca Sevene; Orvalho Augusto; Corssino Tchavana; Charlotta Nilsson; Elias Manjate; Lucia Mabalane Chambal; Vanda dos Muchangos; Júlia Muando (BMJ Public Health, 2025)
Introduction Globally, more than 254 million people are living with hepatitis B virus (HBV), and 7.4% of the people living with HIV (PLHIV) are coinfected with HBV. More than 70% of them reside in Africa. We aimed to describe the characteristics of newly diagnosed antiretroviral treatment (ART)-naïve HIV/HBV co-infected and HIV monoinfected patients.Methods This cross-sectional study included newly HIV-diagnosed ART-naïve patients recruited at Mavalane Health Centre located in a periurban area of Maputo City. Between May 2021 and November 2022, all patients over 18 years old were enrolled and screened for hepatitis B surface antigen (HBsAg). Data on socio-demographic and clinical characteristics, haematology, liver and kidney function tests, CD4+T cell counts, serological markers of hepatitis B (IgM Core hepatitis B antibody, hepatitis B e antigen, and hepatitis B e antibody), HIV and HBV viral loads were assessed using standard procedures.Results A total of 1106 participants were included. The age of the participants ranged from 18 years to 71 years with a median of 34.0 (IQR: 28.0–42.0) years, 513 (46.4%) were men and HBsAg was reactive in 81 participants, yielding a co-infection rate of 7.3%. Being male (OR, 1.72; 95% CI, 1.06 to 2.83) or a sex worker (OR, 3.69; 95% CI, 1.10 to 10.58) was associated with the co-infection. The median Aspartate Aminotransferase-Platelet Ratio Index (APRI) of the HIV/HBV co-infected was 0.5 (IQR 0.3–1.1), with 40/81 (49.4%) presenting with an APRI>0.5. Overall, 67/81 (80.2%) of the co-infected people were HBeAg-negative. The median APRI was 0.5 (IQR, 0.3–1.1) for the HBeAg-negative and 0.7 (IQR 0.3–1.4) for the HBeAg-positive subjects. The median HBV-DNA was 258.0 IU (IQR, 10.0–4974.5) for the HBeAg-negative and 746 287.0 IU (IQR 2720.0–49 899 213.0) for the HBeAg-positive subjects. Two (3.0%) HBeAg-negative and one (7.1%) HBeAg-positive subjects presented with hepatocellular carcinoma.Conclusion These data confirm the high prevalence of HIV/HBV co-infection in Mozambique and bring new data related to HBeAg status, reinforcing the need to test all PLHIV for HBV and to integrate the management and monitoring of hepatitis B and liver disease-specific tests in public ART programmes to predict and reduce the occurrence of HBV complications and mortality.